Anti-arthritic effects of 6-mercaptopurine and its derivatives in arthritis-induced model, In vitro and In vivo - Che Ku Daud, Che Ku Dahlan (2020)
Rheumatoid arthritis (RA) is a chronic inflammatory and autoimmune diseases which causes synovia and joint deformity characterized by abnormal immune condition implicating the synovial fibroblast cell layers and synovium infiltrates further resulting in progressive joints destruction. In this study, four thiopurine compounds namely, 6- mercaptopurine (6-MP), 6-MP riboside, 6-thioguanine (6-TG) and 6-thioxanthine (6- TX) with diclofenac (a non-steroidal anti-inflammatory drug; NSAID) as positive control were screened for their cytotoxicity and anti-inflammatory properties by evaluating the cell cytotoxicity and the nitric oxide (NO) inhibitory activities upon activated fibroblast synoviocytes (HIG-82) and macrophage (RAW 264.7) cell lines with phorbol-12- myristate acetate (PMA) and lipopolysaccharide (LPS), respectively. The preliminary screening results have shown that all the thiopurine compounds did not show any cytotoxic effect on both cell lines at low and medium concentrations. Inhibitory effect of the compounds on nitric oxide production PMA-stimulated HIG-82 had only a small inhibition effect, however excellent inhibition and suppressive activity were observed on RAW 264.7 cell. Meanwhile, at the highest concentration (100 μM) 6-TG and diclofenac had a cytotoxic effect to RAW 264.7 and HIG-82 cell respectively. Further, in vivo study using completed Freund’s adjuvant (CFA)-induced arthritis animal model was conducted to evaluate the therapeutic and toxicity effects of selected thiopurine compounds (6-MP and 6-MP riboside) selected based on in vitro study with different dosages (3, 6 and 10 mg/kg). A repeated oral administration of both compounds showed less toxicity in rats manifested by less alteration in body and organs (liver and kidney) weight, no significant change in full blood count parameters, no significant changes in pivotal liver and kidney biochemical parameters except at high dosage of 6-MP riboside on the liver marker, medium and high dosages of 6-MP on creatinine kidney biomarker, however, no significant toxicity remarks on microscopic histopathology evaluation of both organs. Besides, further experiments were conducted to investigate the pro-inflammatory, suppressive and antioxidative effects of 6-MP and 6-MP riboside on inflammation arthritis induced rats model. 6-MP and 6-MP riboside were observed to inhibit the production of pro-inflammatory cytokines such as TNF-α and IL-6 on the rat blood plasma. Oral repetition treatments of 6-MP at 6 and 10 mg/kg showed a significantly decreased production of pro-inflammatory cytokines, which was similar to diclofenac used. A significant reduction (P<0.05) in the concentration of PGE2 at 6 and 10 mg/kg dosages on plasma-treated 6-MP, respectively when compared to control arthritic also demonstrated. Moreover, plasma peroxide and reduced glutathione showed a significantly better improvement level after treatments. Collectively, this present study suggested that the anti-arthritic and suppressive actions of 6-MP and 6-MP riboside of both in vitro and in vivo model are attributed through interferences in inflammatory mediators and antioxidative regulatory system in the body. In vitro study was obtained a promising where the thiopurine compounds especially 6-MP and 6-MP riboside exhibited the proliferation of HIG-82 and RAW 264.7 cells at suitable dosages. This finding opens new avenues for treating RA during synovial inflammation of RA and the inhibitory effects of 6-MP and 6-MP riboside to suppress inflammatory cells marker such as synovial fibroblast and macrophages by proliferating healthy synoviocytes. The selected dosages of 6-MP and 6-MP riboside in vivo study could be suitable and safer, contributed the best dosages for recovery. A novel knowledge on the pathophysiology of arthritis and its prevention by 6-MP and 6-MP riboside had been revealed throughout this study. Thus, suggests that 6-MP and 6-MP riboside have anti-inflammatory effects by inhibiting the production of pro-inflammatory mediators, enhanced the antioxidant defence system during pathologic condition. 6-MP and 6-MP riboside have therapeutic activity and potentially useful for treating inflammatory conditions as served as a new promising disease-modifying anti-rheumatic drugs (DMARDS) in treating early inflammation arthritis in the future.